La organización de la tutela como tutela de familia o tutela de autoridad: un dilema histórico - Isabel Palomino Diez (Nuevo mundo - Mundos Nuevos, 2008)
The tutelage is eminently a legal institution with a long historical tradition. Traditionally, we have described the systems of trusteeship in terms of those of family and those of authority, although none of them have actually occurred with the sufficient simplicity to deserve that qualification. In addition, they have appeared in time as if neither of them was the magical solution that allowed to guardian minors and handicapped security, promptly and effectively. It is certain that every historical moment influenced the election of each implanted system. We will refer to this briefly, considering the temporary reference conformed by “Las Partidas”, the Civil Code in force through its original and reformed writing. Nevertheless, the conclusion is the same: there are neither permanent nor one hundred effective solutions, but it is certain that the social context in which we live makes us chose an authority of tutelage. Some even refer to, and they may not be wrong, professional tutors.